Improving Power System Stability with Gramian Matrix-Based Optimal Setting of a Single Series FACTS Device: Feasibility Study in Vietnamese Power System - Le Van Dai; Doan Duc Tung; Tran Le Thang Dong; Le Cao Quyen (My University, 2017)
Improving Power System Stability with Gramian Matrix-Based Optimal Setting of a Single Series FACTS Device: Feasibility Study in Vietnamese Power System
Keywords: Power system stability; Gramian Matrix; FACTS device